Leech parasitism of waterfowl in North America - Trauger, David L; Bartonek, James C (Wildfowl, 1977)
Leech parasitism of waterfowl is widespread in North America. Twenty species of ducks, geese, and swans have been infested by leeches, particularly Theromyzon rude and Placobdella ornata. Sites of attachment include the eyes, nasal passages, and body. Information is lacking on the biology and ecology of duck leeches. Their significance as morbidity and mortality factors and their continental distribution should be determined in relation to waterfowl habitats and populations.